Large Bowel Obstruction Subsequent to Resected Lobular Breast Carcinoma: An Unconventional Etiology of Malignant Obstruction - Melissa Amberger; Nancy Presnick; Gerard Baltazar (Case Reports in Surgery)
Introduction. Breast cancer metastasis to the gastrointestinal tract is rare and mostly limited to case reports which recommend consideration of metastasis when breast cancer patients particularly those with invasive lobular carcinoma present with new gastrointestinal complaints. Presentation of case. We report a 50-year-old female who presented with gastrointestinal symptoms of nausea and vomiting determined to be the result of large bowel obstruction secondary to rectosigmoid metastasis and carcinomatosis of breast invasive lobular carcinoma. She was treated with diverting loop sigmoid colostomy for her large bowel obstruction. Discussion. Our case reflects the importance of gastrointestinal surveillance of patients with a history of breast cancer. Current National Comprehensive Cancer Network (NCCN) guidelines for stage I-II breast cancer suggest posttreatment lab and imaging evaluation for metastasis only if new symptoms present. Conclusion. We observed an unusually rapid disease progression, requiring evaluation of new gastrointestinal symptoms. Assessment for GI tract metastatic involvement should be done as early as progression to symptomatic disease can result in need for further invasive surgery in advanced stages of cancer.